Nowe śródlądowe stanowiska halofilnej zielenicy Enteromorpha compressa (L.) Ness w Polsce - Messyasz, Beata; Rybak, Andrzej (My University, 2011)
The new freshwater localities of Enteromorpha compressa were located in Poznań streams: Michałówka, Dworski Rów and Świątnica. The occurrence of this green alga was connected with the great concentration of chlorides and nitrates in the water. Mature thalluses of E. compressa were rich in corrugation, had numerous of long (several cm) proliferations and narrowings at the top parts of the tape. This freshwater form was reached the largeness of the thallus even up to 8 cm widths and 180 cm of the length.
New inland localities of salt -like greenalga Enteromorpha compressa (L.) Ness in Poland
Keywords: Chlorophyta; Enteromorpha compressa; Halophilous macroalgae; Wielkopolska; Stream; Distribution; Freshwater Ulva; Freshwater Enteromorpha; Ulva; Enteromorpha; Ulvophyceae; Ulvaceae